Study of Matter Density Distributions, Elastic Electron Scattering form Factors and Reaction Cross Sections of 8He And 17B Exotic Nuclei - K. Hamoudi, Adel; N. Flaiyh, Gaith; N. Abdullah, Ahmed (Iraqi Journal of Science, 2025)
The ground state densities of unstable neutron-rich 8He and 17B exotic nuclei are studied via the framework of the two-frequency shell model (TFSM) and the binary cluster model (BCM). In TFSM, the single particle harmonic oscillator wave functions are used with two different oscillator size parameters βc and βv where the former is for the core (inner) orbits and the latter is for the valence (halo) orbits. In BCM, the internal densities of the clusters are described by single particle Gaussian wave functions. Shell model calculations for the two valence neutrons in 8He and 17B are performed via the computer code OXBASH. The long tail performance is clearly noticed in the calculated neutron and matter density distributions of these nuclei. The structure of the two valence neutrons in 8He and 17B is found to be a mixed configurations with dominant (1p1/2)2 and (2s1/2)2, respectively. Elastic electron scattering proton form factors for 8He and 17B are studied using the plane wave born approximation (PWBA). It is found that the major difference between the calculated form factors of unstable nuclei [8He, 17B] and those of stable nuclei [4He, 10B] is the difference in the center of mass correction which depends on the mass number and the size parameter β (which is assumed in this case as the average of βc and βv). The reaction cross sections for 8He and 17B are studied by means of the Glauber model with an optical limit approximation using the ground state densities of the projectile and target, where these densities are described by single Gaussian functions. The calculated reaction cross sections of 8He and 17B at high energy are in good agreement with the experimental data. The analysis of the present study supports the halo structure of these nuclei.